Calcium-, magnesium-, and yttrium-doped lithium nickel phosphate nanomaterials as high-performance catalysts for electrochemical water oxidation reaction - Nasir Mehwish Huma; Niaz Hajira; Yunus Naila; Ali Urooj; Khan Safia; Butt Tehmeena Maryum; Naeem Hina; Li Hu; Habila Mohamed A.; Janjua Naveed Kausar (Nanotechnology Reviews, 2024)
Electrochemical water oxidation over high-efficiency (Ca, Mg, or Y) doped lithium metal (Ni) phosphate electrocatalysts